COMMUNITY-BASED INTERVENTION MODEL FOR PREECLAMPSIA PREVENTION THROUGH RIVER FISH CONSUMPTION AND PERIODIC MATERNAL-FETAL MONITORING IN TAHTUL YAMAN, JAMBI - Herlambang, Herlambang; Fitri, Amelia Dwi; Puspasari, Anggelia; Kusdiyah, Erny; Enis, Rina Nofri; Maharani, Citra; Shafira, Nyimas Natasha Ayu; Aurora, Wahyu Indah Dewi; Hasmita, Debby (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Preeclampsia is a leading cause of maternal and perinatal complications. Preventive strategies based on local food resources offer a sustainable approach aligned with the Sustainable Development Goals. This study describes a community-based intervention integrating nutrition, health education, and periodic monitoring among pregnant women in the Puskesmas Tahtul Yaman area, located along the riverside in Jambi. The intervention applied the Health Belief Model to enhance perceived benefits and reduce barriers, the Theory of Planned Behavior to strengthen attitudes and behavioral control, and Knowles’ Adult Learning Theory for contextual learning. Activities were conducted in two phases. In the first phase (gestational age 26–28 weeks, trimester 2), pregnant women attended sessions on preeclampsia and safe fish consumption, supported by cooking demonstrations using nutrient-dense river fish. They received fish-based meals twice weekly for six weeks. Maternal health was monitored through blood pressure, weight gain, and symptoms, while fetal well-being was assessed by ultrasonography. The second phase, eight weeks later (trimester 3), repeated maternal examination and ultrasonography for follow-up of pregnancy. None of the participants developed hypertension, fetal growth matched gestational age, and mothers showed improved knowledge of preeclampsia and its prevention, particularly through fish consumption. This community-driven model demonstrates the effectiveness of combining local nutrition, adult learning strategies, and regular maternal-fetal monitoring. It highlights a feasible, culturally sensitive, and sustainable approach to strengthen maternal health and prevent preeclampsia in resource-limited settings. Keywords:; community-based intervention; Health Belief Model; maternal health; preeclampsia prevention; river fish consumption